Essays on Housing Markets - Claes Bäckman (Copenhagen Business School (CBS), 2017)
In Denmark and in many countries around the world, housing markets are of considerable importance for households and policy-makers alike. As the boom and bust in the US and Danish housing market so aptly demonstrated, disruptions in the housing market potentially have wide-ranging consequences for individual households and for the aggregate economy. Housing is important because we all have to live somewhere, but also because it serves as a considerable source of both wealth and debt. As such, housing market policy can not only create vast benefits for many, but can also have substantial negative impacts for all, and should therefore be a topic of major interest for economists and policy makers alike. This Ph.D. thesis, entitled “Essays on Housing Markets”, analyzes the Danish housing market during the 2000s, with a focus on how policy changes affected house prices and how changes in house prices affect households. While independent, each chapter in this thesis attempts to contribute to our understanding of how housing markets function, and has important lessons for policy-makers and economists around the world.
hdl:10398/9438
Keywords: 650